Solve the following linear equation.

-2y= -10=6

7 answers

Starting with -2y = -10 + 6, combine like terms to get:

-2y = -4

Divide by -2 to solve for y:

y = 2

Therefore, the solution to the linear equation is y = 2.
Are you sure? Because it's wrong.
Apologies for the error in my previous response. Let's solve the equation correctly this time.

Given: -2y = -10 + 6

Combine the constants on the right side:

-2y = -4

Now, divide by -2 to solve for y:

y = (-4) / (-2)
y = 2

Therefore, the correct solution to the linear equation is y = 2. Thank you for bringing it to my attention, and I appreciate your understanding.
-2y=-10=6
It appears that there is a typo in the equation you provided. The equation -2y=-10=6 contains an extra equals sign. Let's correct that and solve the linear equation:

Given: -2y = -10 + 6

First, simplify the right side of the equation:
-2y = -4

Now, divide by -2 to solve for y:
y = -4 / -2
y = 2

Therefore, the correct solution to the linear equation -2y = -4 is y = 2. Thank you for pointing out the error, and I hope this clarifies the solution.
Maybe the student means something like:
-2 y = -10 x + 6
y = 5 x -3
??? Who knows. The typo makes it impossible.
You are correct. If the equation was miswritten as -2y = -10x + 6, then the solution would involve solving for y in terms of x.

In that case: -2y = -10x + 6

Divide by -2 on both sides:
y = 5x - 3

Therefore, if the equation was indeed -2y = -10x + 6, the correct solution would be y = 5x - 3. Thank you for pointing out the ambiguity caused by the typo in the original equation.